An Application of a Communication Concept for Reducing Energy Drink among Male Agriculturist at Huai Rat District, Buri Ram Province - Natsuwan, Suchart (Journal of Health Science of Thailand, 2017)
Certain behavior is the main cause of both long and short term health problems. This includes over consumption of energy drink which is rich with stimulants. The propaganda could tempt drinkers to become addicts. This study was conducted among male agriculturists aged 15 years and above at Huai Rat District, Buri Ram Province. The purpose of this quasi-experimental research was to study the knowledge level, attitudes and practices among energy drink consumers, using the application of Berlo’s communication model, from February 2010 to April 2010, the study subjects were 120 male agriculturists. They were divided into two groups; 60 in the experimental group and 60 in the comparison group. The Berlo’s model was applied for training and home visits. The data were collected before and after the experiment by interview questionnaires. Data were analyzed and presented in terms of frequencies percentages, mean and standard deviation while paired t-test, independent t-test were employed in order to establish differences of results. The results revealed that after receiving the intervention, the experimental group had been more knowledge, able improved attitudes and practices better than before the interventions and scored higher than the comparison group (p < 0.001). In conclusion, this research findings showed the application of Berlo’s communication concept on the health education program could reduce energy drink consumption among male agriculturists. So this education program can be implemented in areas with similar problems to reduce drinker’s health problems.